Mental Health Problems Related to COVID-19: A Call for Psychosocial Interventions in Uganda - Ainamani, Herbert E.; Gumisiriza, Nolbert; Rukundo, Godfrey Zari (Psychological Trauma: Theory, Research, Practice, and Policy, 2020)
As different countries grapple with COVID-19, stringent measures aimed at controlling its spread have been put in place. However, these preventive measures coupled with the fear of contracting the disease are likely to have negative effects on the mental health of the general population. We describe the containment measures taken by the government of Uganda and highlight how these measures are likely to impact the mental health of different groups of people. We also propose future directions and interventions on mental health problems resulting from COVID-19 pandemic
Keywords: COVID-19; Mental health; Psychosocial intervention; Uganda-Africa